STRUCTURAL AND MECHANICAL PROPERTIES OF 2D GRAPHENE: A STUDY OF MOLECULAR SIMULATIONS - Van Dung Mai (Tạp chí Khoa học Đại học Đà Lạt)
A graphene model consisting of 12,000 atoms is yielded by molecular dynamics simulation in two-dimensional space. The structural evolution of the graphene model is analyzed in terms of total energy per atom, heat capacity, radial distribution function, coordination number distribution, bond angle distribution, and visualization. The results show that spontaneous melting of the graphene model occurs at approximately Tm = 6500 K. In addition, our simulation of the atomic configuration shows that the coexistence of crystalline and melted regions near the melting temperature confirms the first-order behavior of the phase transition. The Lindemann criterion for the 2D case is calculated and used to observe the appearance of liquid-like atoms. The atomic mechanism is analyzed based on the occurrence and growth of these liquid-like atoms. The Young’s modulus of the graphene model at an uniaxial strain rate of 108 s-1 is 1.014 TPa, indicating good agreement with the experimental data. This research brings substantial practical benefits to industries looking to leverage the unique thermal and mechanical characteristics of graphene.